Literature study on the effect of exposition factors on image quality in the aspect of gray degree - Theos, Nicholas Austrin (Universitas Riau, 2025)
This literature study aims to examine the influence of exposure factors on the quality of radiographic images in the field of radiodiagnostics. Three scientific journals were used as research materials, focusing on adjusting tube voltage (kV) and exposure time (mAs) to optimize image quality. Experiments were conducted using Computed Radiography (CR) and Digital Radiography (DR) on different phantoms, such as water in a plastic bag as phantom, ossa manus phantom (hand), and abdominal phantoms. The results of the study indicate that the optimal combination of tube voltage and exposure time varies depending on the density and thickness of the tissues being examined. In conclusion, the proper adjustment of exposure factors is key to obtaining high-quality radiographic images for diagnosing diseases or lesions.